Peningkatan Keterampilan Kerja Pemuda melalui Pelatihan SDM Berbasis Kompetensi di Yayasan Tajaul Karomah Desa Situ Gandung Kabupaten Tangerang - Suryani, N Lilis; Darmadi, Darmadi; Susanto, Noto (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Youth unemployment remains a pressing issue in many rural areas, including Desa Situ Gandung, Kabupaten Tangerang, where limited access to skill-based education hinders employment opportunities. In response, this Community Service Program (PKM) was conducted to enhance youth employability through competency-based human resource training. The program aimed to equip participants with practical knowledge and skills aligned with current labor market demands. The PKM activity was held at Yayasan Tajaul Karomah, Desa Situ Gandung, on April 12–13, 2025, and was carried out by 15 lecturers from Universitas Pamulang. A total of 38 community members from the village participated in the two-day program. The implementation method included structured presentations, interactive discussions, and question-and-answer sessions to ensure effective knowledge transfer and participant engagement. The results demonstrated a significant increase in participants' understanding of job competencies, personal development strategies, and workplace readiness. Participants actively engaged in discussions, indicating improved motivation and awareness of career planning. Furthermore, the collaborative approach between academics and local institutions fostered a positive environment for sustainable community development. Overall, the PKM initiative successfully contributed to the empowerment of youth in Desa Situ Gandung by strengthening their skills and readiness for employment. Future programs are expected to build on this foundation to expand outreach and impact.